Estimating the effect of monopsony power on elasticity estimates. Issue 3 (14th January 2016) - Yamaura, Koichi; Featherstone, Allen M.
ABSTRACT: Love and Shumway (1994) developed a nonparametric deterministic test for monopsony market power using a normalized quadratic restricted cost function with one input for which the firm has potential market power. This research examines monopsony power using Lau's Hessian identity relationships based on the empirical properties of duality theory. Lau's Hessian identity shows the Hessian matrices are equal under pure competition using an unrestricted profit function, restricted profit function and production function approach. We examine how market power changes in the monopsony case using Lau's Hessian identity relationships. Results show that there is a difference between the unrestricted and restricted profit function results under monopsony power. The important implication is that if an input or output is potentially in a market subject to market power, that input or output should be modelled as a fixed input or output to correctly recover the underlying technology.